How Well do Canadian Distance Education Students Understand Plagiarism? - Kier, Cheryl Ann (International Review of Research in Open and Distributed Learning)

(untitled) (Athabasca University Press (AU Press), 2014)
This project ascertains how well students taking online, distance education courses at a Canadian university recognize plagiarised material and how well they paraphrase. It also assesses the types of errors made. Slightly more than half of 420 psychology students correctly selected plagiarised phrases from four multiple choice questions. Only a minority was able to rewrite a phrase properly in their own words. A more diverse sample of university students also had difficulty recognizing plagiarised passages from multiple choice options. The poor ability of students to identify plagiarised passages may suggest poor understanding of the concept. Students may benefit from training to improve their understanding of plagiarism.